Oxford handbook of primary care and community nursing - Brook, Judy; McGraw, Caroline; Thurtle, Val (Oxford : Oxford University Press, 2020)
This handbook provides easily accessible, contemporary, and evidence-based material, to act a reference or first point of enquiry for practitioners working in the diverse areas of primary and community care.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 18, 2020).
Keywords: Primary nursing; Community health nursing; Primary care (Medicine)